Optimized Blood Volume Monitoring during Hemodialysis Procedure based on Ultrasonic Speed Measurement - Nafisi V. R.; Eghbal M. (Journal of Biomedical Physics and Engineering, 2019)
Fast reduction of blood water volume due to ultra-filtration via hemodialysis machine and critical threshold of blood water volume can result in clinical complications such as hypotension. When blood water volume reduces during hemodialysis process, the concentration of blood forming elements will increase. One of the methods for the monitoring of the concentration changes is ultrasonic speed measurement. In this paper, we optimize the ultrasonic speed measurement method in such a way that it would be compatible with conventional air detector in a hemodialysis machine. Air bubble detecting and the relative blood water volume estimating can be achieved by adding the “sing-around” ultrasonic speed measurement method to the current hemodialysis machine; air bubble detection is achieved by monitoring the decline in the ultrasonic wave amplitude (because of air bubbles) and the protein concentration measurement is achieved by measuring the transit time of the wave. Therefore, the optimized method can be applied to the air detection device of a hemodialysis machine. Citation: Nafisi V. R, Eghbal M. Optimized Blood Volume Monitoring during Hemodialysis Procedure based on Ultrasonic Speed Measurement. J Biomed Phys Eng. 2019;9(3):373-380. https://doi.org/10.31661/jbpe.v9i3Jun.675.